Global microRNA level regulation of EGFR‐driven cell‐cycle protein network in breast cancer - Uhlmann, Stefan; Horvát, Emöke-Ágnes; Zweig, Katharina A.; Wiemann, Stefan (Molecular systems biology, 2012)
The EGFR‐driven cell‐cycle pathway has been extensively studied due to its pivotal role in breast cancer proliferation and pathogenesis. Although several studies reported regulation of individual pathway components by microRNAs (miRNAs), little is known about how miRNAs coordinate the EGFR protein network on a global miRNA (miRNome) level. Here, we combined a large‐scale miRNA screening approach with a high‐throughput proteomic readout and network‐based data analysis to identify which miRNAs are involved, and to uncover potential regulatory patterns. Our results indicated that the regulation of proteins by miRNAs is dominated by the nucleotide matching mechanism between seed sequences of the miRNAs and 3′‐UTR of target genes. Furthermore, the novel network‐analysis methodology we developed implied the existence of consistent intrinsic regulatory patterns where miRNAs simultaneously co‐regulate several proteins acting in the same functional module. Finally, our approach led us to identify and validate three miRNAs (miR‐124, miR‐147 and miR‐193a‐3p) as novel tumor suppressors that co‐target EGFR‐driven cell‐cycle network proteins and inhibit cell‐cycle progression and proliferation in breast cancer. - Synopsis - A genome‐wide microRNA (miRNome) screen coupled with high‐throughput monitoring of protein levels reveals complex, modular miRNA regulation of the EGFR‐driven cell‐cycle network, and identifies new miRNAs that can suppress breast cancer cell proliferation. - We interrogated, for the first time, a mammalian oncogenic signaling network with the miRNome and report the outputs at the protein level. Whole‐genome microRNA (miRNA) effects on a given protein are generally mild, supporting a fine‐tuning role for miRNAs, and these effects are dominated by sequence‐matching mechanisms. We developed a novel network‐analysis methodology with a bipartite graph model to identify proteins co‐regulated by miRNAs. Besides the sequence‐based mechanism, our results demonstrated that miRNAs simultaneously regulate several proteins belonging to the same functional module. We identified three miRNAs, miR‐124, miR‐147 and miR‐193a‐3p, as novel tumor suppressors that co‐regulate EGFR‐driven cell‐cycle network proteins, and inhibit cell‐cycle progression and proliferation in breast cancer. Our results demonstrate the potential to steer miRNA research toward the network level, underlining the need for systematic approaches before positioning miRNAs as drugs or drug targets.
Gesehen am 27.09.2018